Strategies to Overcome Children's Tantrums Based on Martin Heidegger's Existentialist Perspective In Primary School - Irfan Irfan; Sri Atin; Rusdy Iskandar; Kharisma Romadhon (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The development of negative emotions is a problem that manifests in children with tantrums, such as excessive anger. Tantrums can be pathological, so early identification can help teachers handle them in order to prevent long-term negative effects. The study in this paper aims to identify strategies to overcome tantrums in children based on the existentialist philosophy of Martin Heidegger in terms of building responsibility within themselves through four aspects. The use of the research method is qualitative with a case study approach. The data analysis is the triangulation of data acquisition techniques, which includes observation, interviews, and documents. Observations were conducted on one tantrum-prone child in the second grade. Interviews were conducted with the second-grade and the guidance counselor teachers to determine the appropriate strategies. The research results indicate the findings of several ways of the second-grade teacher strategies and the guidance counselor teacher in overcoming tantrum-prone children at school. Firstly, individual support is required. Secondly, opportunity is given for tantrum-prone children to express their emotions in a conducive environment. Thirdly, opportunity is provided to children to foster their self-awareness to cultivate tolerance among peers. Fourthly, the opportunity is intended for children to express the circumstances that make their tantrums up. Fifthly, the opportunity is addressed to provide rewards in the form of verbal reinforcement when tantrum-prone children exhibit positive behavior. Sixthly, the opportunity refers to providing a humanistic approach, redirecting the child's emotions in a conducive environment, and providing a sense of safety and security by hugging the children when they are in high levels of emotional distress during tantrums. The research conclusion is that strategies for overcoming tantrum-prone children consist of six methods, including opportunities to provide individual support, express their emotions and circumstances, provide children’s self-awareness building, give rewards, and conduct a humanistic approach.